The Impact of Dissolved Organic Matter in Natural Receiving Systems on the Formation Potential and Toxicity of Disinfection By-products: Insights from Origins, Chemical Properties, and Transformations - Li, Wei-Yu; Chen, Yun; Wang, Wen-Long; Chen, Yan-Lin; Wu, Qian-Yuan (Current pollution reports, 2025)
Purpose of Review This study aims to examine the role of dissolved organic matter (DOM) as a key precursor to disinfection by-products (DBPs) in aquatic environments. Key objectives include elucidating how DOM sources, chemical properties, and environmental transformations influence DBP speciation and toxicity. The study also evaluates strategies for mitigating DBP risks in drinking water treatment and identifies critical knowledge gaps in linking DOM dynamics to DBP toxicity profiles. Recent Findings Recent studies highlight that the sources of DOM and its chemical characteristics, including SUVA 254 and humification index (HIX), strongly influence disinfection by-product formation potential (DBPFP). Photochemical and microbial transformations significantly alter the reactivity of DOM, with photodegradation typically reducing DBPFP while biodegradation increasing it. Despite these findings, the relationship between DOM transformations and DBP toxicity remains underexplored. Advanced mass spectrometry and fluorescence-based techniques have improved the ability to characterize DOM, offering new insights into the molecular-level dynamics of DBP formation. While traditional water treatment methods remain essential, enhanced coagulation, adsorption, and advanced oxidation processes are increasingly necessary to efficiently remove DOM and mitigate DBP formation. Summary This review provides a comprehensive examination of the DOM-DBP relationship, offering insights into the speciation and toxicity of DBP. It is highlighted that the sources, chemical properties, and natural transformations of DOM complicate the DBP precursor pool, affecting DOM reactivity and DBP production during disinfection. Advances in analytical techniques could improve our understanding of molecular-level interactions between DOM and DBP. Future research should prioritize comprehensive DOM characterization and predictive models to link DOM subfractions with toxicity explicitly. Furthermore, enhanced removal strategies must be developed to balance disinfection efficacy with minimized health and ecological risks, thereby ensuring water quality safety.